Transition of Patients with Esophageal Atresia to Adult Care: Results of a Transition-Specific Education Program - Dingemann, Jens; Szczepanski, Rüdiger; Ernst, Gundula; Thyen, Ute; Ure, Benno; Goll, Melanie; Menrath, Ingo (European Journal of Pediatric Surgery, 2017)
Aim of the Study A history of esophageal atresia (EA) may result in chronic morbidity. The transition of patients from pediatric to adult care has been recognized as an important factor to maintain disease-specific follow-up and prevent exacerbation of chronic disease. Patient education is recognized as a necessary part of transition programs for children with chronic diseases. Structured education programs for patients with EA have not yet been developed. We aimed to evaluate the efficacy of a transition-specific educational program in adolescents with a history of EA.Methods An ethical approval was obtained. Patients with a history of EA (age 14–21 years) and their parents were invited to participate in a 2-day transition-specific educational program. Overall, 29 patients and 25 parents were recruited out of whom 10/7 were allocated to the intervention group (program) and 19/18 to the control group (no program). Subjective satisfaction (ZUF-8) and expected effects of the program on the future course of the disease, transition-specific knowledge (standardized questionnaire addressing organizational and health-related aspects of transition), health-related quality of life (DISABKIDS), and confidence for self-management (Patient Activation Measure-13) were measured with appropriate psychological instruments. Nonparametric tests were used for statistical analysis.Main Results Subjects participating were highly satisfied with the program (patients 26/32 points, parents 25/32; ZUF-8). Overall, 90% of the patients and 67% of the parents anticipated a positive effect on the future course of the disease. Patient's transition-specific knowledge was low before the program (36% correct answers). It improved by 18% after the intervention (56% correct answers; p = 0.004). It did not change in the control group (54 vs. 52%; n.s.). Parent's transition-specific knowledge did not change after the intervention (66 vs. 67% correct answers; ns). In patients, there were no detectable effects on health-related quality of life (79.7 intervention vs. 81.5 controls; DISABKIDS general score) or self-management (44.4 intervention vs. 41.4 controls; PAM-13).Conclusions We identified a deficit of transition-specific knowledge in adolescents with a history of EA. These patients benefit from a transition-specific education program. Thus, the transition to adult care may be facilitated resulting in an improved long-term care of patients with EA.
Keywords: transition; esophageal atresia; patient education; chronic disease; modus